Purchasing behavior of professional buyers in out of home industry : The significance of price in the purchasing behavior - Husu, Mikko (My University, 2022)
This research is observing purchasing behavior of professional buyers in the media industry. The study focuses on media agency personnel who are specialized in out of home advertis-ing. The research is conducted in three countries via online survey. The countries being Fin-land, Sweden, and United Kingdom. The key concepts of the thesis are out of home advertis-ing, cross cultural theory, media agencies, relationship marketing and purchasing behavior of professional buyers. Purchasing is important for companies because it has effect on the bottom line. Purchasing forms considerable portion of the turnover in most organizations. Outsourcing the purchases has become more common and it is expected to increase in the future. One of the most im-portant tasks of media agencies is to purchase media for their customers cost effectively. They create significant cost advantages and can increase the profitability of their clients. Me-dia agencies are seemed as crucial partners in the purchasing of media. The analysis of the study is conducted with quantitative analysis where the focus is on the relationship between four independent factors and the dependent factor. The four inde-pendent factors of organizational buying behavior are environmental force, organizational force, group force and individual force. The dependent factor is the importance of price in purchasing. These relationships are analyzed and whether they have significant influence. Then the relationships are moderated with masculinity dimension. Masculinity is a dimension from a model by Hofstede (1980) where he observed cross cultural theory from the perspec-tive of four different dimensions. The study has two objectives. The first concerns delivering data regarding purchasing behav-ior of professional buyers in the media industry and the second one gives an answer whether the masculinity dimension has effect on the purchasing behavior.

Tässä työssä tutkitaan media-alan ammattiostajien ostokäyttäytymistä. Tutkimus keskittyy mediatoimistojen henkilökuntaan ja vielä tarkemmin niihin henkilöihin, jotka ovat ulkomai-nosalaan erikoistuneita. Työ toteutetaan kolmessa markkinassa verkkolomakkeen avulla. Nämä kolme maata ovat Yhdistyneet kuningaskunnat, Suomi ja Ruotsi. Työn pääaiheita ovat ulkomainonta, kulttuurien väliset teoriat, mediatoimistot, suhdemarkkinointi ja ammattiosta-jien ostokäyttäytyminen. Ostot ovat tärkeitä yrityksille, koska niillä on suora vaikutus yritysten tulokseen. Ostot vaikut-tavat merkittävästi yritysten liikevaihtoon. Ostojen ulkoistaminen on yleistynyt ja sen odote-taan kasvavan entisestään tulevaisuudessa. Yksi tärkeimmistä mediatoimistojen tehtävistä on ostaa mediaa heidän asiakkailleen kustannustehokkaasti. Mediatoimistot luovat merkittä-viä hintaetuja ja voivat kasvattaa näin asiakkaidensa kannattavuutta. Mediatoimistoja pide-tään tärkeinä kumppaneina median ostamisessa. Tutkimuksen analysointi toteutetaan kvantitatiivisella analyysillä, joka keskittyy neljään riip-pumattomaan tekijään ja yhteen riippuvaan tekijään. Nämä neljä riippumatonta tekijää ovat ympäristön vaikutus, organisaation vaikutus, ryhmän vaikutus ja yksilön vaikutus. Tutkimuk-sen riippuva tekijä on hinnan merkitys ostamisessa. Näiden neljän riippumattoman muuttu-jan suhdetta tutkitaan ja määritetään, onko niillä merkittävää vaikutusta hinnan merkityk-seen. Tämän jälkeen suhteita arvioidaan maskuliinisuuden avulla ja lisääkö maskuliinisuus hinnan merkitystä ostamisessa. Maskuliinisuus on yksi Hofstede:n (1980) luoman mallin nel-jästä tutkittavasta osa-alueesta. Kyseinen tutkimus tarkasteli kulttuurien välisiä eroja kansalli-sessa mittakaavassa. Tutkielmalla on kaksi tavoitetta. Ensimmäinen liittyy tietoon ammattiostajien ostopäätöksistä media-alalla ja toinen tutkimuskysymys vastaa miten maskuliinisuus vaikuttaa ostokäyttäy-tymiseen.
Keywords: purchases; marketing; communication; media; purchasing; business-to-business marketing; fi=Markkinointi|en=Marketing|; Master's Degree Programme in International Business